Tobacco use and lung cancer - Juan W Zinser (Instituto Nacional de Salud Pública, 2019)
Smoking is the main cause of lung cancer. It plays a role in the etiology, and depending on the intensity and duration, it also has an influence on histology, stage and therapeutic outcome. Therefore, it is never too late to stop smoking. Tobacco smoke is so toxic, that there is no safe smoking modality. Filters, light cigarettes, pipes, water pipes, etc. are prohibitively harmful. In addition, the electronic nicotine delivery systems, besides promoting addiction, cause acute respiratory and cardiovas¬cular effects. In addition, even though long-term consequences are yet to be known, cell proliferation and tumor progression have been identified. Tobacco control efforts should look at all these new products as its main threat.